2019
DOI: 10.15361/1984-5529.2019v47n4p426-433
|View full text |Cite
|
Sign up to set email alerts
|

Substrates and duration for conducting the safflower seed germination test

Abstract: Safflower (Carthamus tinctorius) is an annual, rustic plant that has multiple uses. Seed laboratory analysis showed discrepancies in germination depending on the substrate used in a given lot. Therefore, studies are needed to determine the best substrate and the time required to perform the first and final count of the safflower seed germination test. Five lots were used, which were characterized by moisture degree and thousand seed weight. These lots were evaluated on four substrates (between paper, on paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Germination test: eight repetitions of 25 seeds were sown in transparent acrylic boxes with lids (11.0 × 11.0 × 3.5 cm) containing "blotting paper" as substrate type, then the seeds were covered with one of the same paper, moistened with a volume of water (mL) equivalent to 2.5 times the mass of dry paper (g) (Brasil, 2009). The final count on the eighth day after the test installation (Gama et al, 2019) counting the number of normal, abnormal and dead seedlings, as described in the RAS (Brasil, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Germination test: eight repetitions of 25 seeds were sown in transparent acrylic boxes with lids (11.0 × 11.0 × 3.5 cm) containing "blotting paper" as substrate type, then the seeds were covered with one of the same paper, moistened with a volume of water (mL) equivalent to 2.5 times the mass of dry paper (g) (Brasil, 2009). The final count on the eighth day after the test installation (Gama et al, 2019) counting the number of normal, abnormal and dead seedlings, as described in the RAS (Brasil, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…First count of germination: performed in conjunction with the twinning test, with a count of the number of normal seedlings on the third day after the test was installed (Gama et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eight replicates of 25 seeds were placed to germinate between two layers of paper (blotting paper) inside transparent plastic boxes (11.0 x 11.0 x 3.5 cm). The paper was moistened with a volume of water (mL) equivalent to 2.5 times the mass of the dry paper (g) (Brasil 2009), with final count the seeds germinated at eight days, according to Gama et al (2019).…”
Section: Germination Testmentioning
confidence: 99%
“…Similarly, a study by R. C. da, Grzybowski and Panobianco (2016) with maize seeds reported that, depending on the substrate, higher and lower vigor lots could show similar performances, proving that the substrate has a greater effect on the results than the physiological quality of the seeds in germination and seedling vigor tests. However, there have also been reports that high vigor fodder pea and safflower lots were less demanding on substrate conditions than low vigor lots (Gama et al, 2019;Machado, Martins, Silva Cruz, Assis, 2019b).…”
Section: Germination and First Count Testmentioning
confidence: 99%